2013
DOI: 10.1111/fct.12006
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of herbal medicine use by UK patients/consumers: a systematic review of surveys

Abstract: Objective To estimate the prevalence of herbal medicine (HM) use in the UK. Methods The databases AMED, CINAHL, COCHRANE, EMBASE and MEDLINE were searched for peer‐reviewed surveys published between January 2000 and September 2011. The authors’ own departmental files were also manually searched for relevant references. Results Ten surveys were included with a total of 20 601 participants. All surveys had major methodological limitations. Across all surveys, the average prevalence rate for a range of time perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 22 publications
(80 reference statements)
0
9
0
Order By: Relevance
“…Some limitations, however, also need to be considered. The primary weakness of our study was the lack of data on complementary and alternative medicines reported to be used by a considerable proportion of patients with cancer, as well as over‐the‐counter medication, which is also frequently used . Another limitation was the lack of data on the reasons for discontinuation of drug treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Some limitations, however, also need to be considered. The primary weakness of our study was the lack of data on complementary and alternative medicines reported to be used by a considerable proportion of patients with cancer, as well as over‐the‐counter medication, which is also frequently used . Another limitation was the lack of data on the reasons for discontinuation of drug treatment.…”
Section: Discussionmentioning
confidence: 99%
“…For many years herbal products have been generally considered safe and have become increasingly popular especially in combination with conventional medicines and are used usually without consultation with a healthcare professional [2,3] . No studies have investigated the co-administration of herbal medicines with dabigatran, rivaroxaban, apixaban or edoxaban [5] .…”
Section: Discussionmentioning
confidence: 99%
“…The use of herbal products has become increasingly popular, especially in combination with conventional medicines and usually without the advice of a healthcare professional [2,3] . However, it is difficult to predict the pharmacokinetic and/or pharmacodynamic interactions when herbal products, such as ginger and cinnamon, are combined with DOACs.…”
Section: Introductionmentioning
confidence: 99%
“…[ 64 ] Moreover, a review study in England showed that almost one-third of the cancer patients were provided with supplementary care from the time of diagnosis, and the challenge which cancer patients may face in this regard is the possibility of causing harm in some of these methods. [ 43 ] In Jordan, at King Hussein Cancer Center, some supplementary care is offered along with the main cancer treatments. [ 65 ] In this regard, in 2013, a study was conducted in this center by Al-Omari et al .…”
Section: Discussionmentioning
confidence: 99%